Thermostable virus portal proteins as reprogrammable adapters for solid-state nanopore sensors - Benjamin Cressiot (Nature Portfolio, 2018)
Solid state nanopores are robust but the sizing can be variable, whereas protein nanopores are precisely sized but lack robustness. Here the authors cork a solid state nanopore with the DNA-translocating portal protein from the virus G20c to obtain a lipid-free hybrid nanopore that can sense various biopolymers.